Classifying the legal system of the Philippines a preliminary analysis with reference to labor law - Mahy, Petra; Sale, Jonathan P. (2012)
In some recent international literature on comparative law and economics, the Philippines has been misclassified as a civil law family country. This paper provides a corrective to this view by tracing the foreign influences on the Philippine legal system as a whole, and on the development of labor law specifically, to demonstrate that American common law influence has far outweighted that of the Spanish civil law heritage. However, this is only part of the story, as in the post-colonial era, the law of the Philippines has progressively reflected local political and economic conditions and in many instances has developed without any direct reference to external models. Hence this paper argues that the Philippines is more rightly classified as a hybrid legal system dominated by common law traditions, but that such a classification will still not adequately describe the nature of the current system.
Keywords: Law and economics; Labor laws